The Effect of Applying Standard Costing Methods in Control of Costs Elements : A Field Study of Some Industrial Companies in Sudan - د. الفاتح الفضل محمد الحاج; أ. موسى الطيب أحمد العبيد (White Nile Journal for Studies and Research, 2022)
The study problem was represented in the inability of industrial companies to control the cost of product. The study aimed to identify the effect of the applying of standard costing methods in control of costs. The study used the historical, inductive, deductive, analytical descriptive Approach. The study reached a set of results: the full-year standard help to the allocation of direct raw materials, applying the standard costs system in the institution helps analyze direct costs deviations. The study recommended: work in the overall variable cost style because it helps to identify direct wage deviations. Increased attention to the average of actual cost style for many years it helps to follow the direct wages costs.